Current Status of Marine Snakes from Jaffna Peninsula, Sri Lanka with Description of Hitherto Unrecorded Hydrophis fasciatus fasciatus (Schneider, 1799) [2008] - Abyerami, S.; Sivashanthini, K. (My University, 2008)
As only a few study reported on sea snakes of Sri Lanka, a study was undertaken from June 2003 to November 2004 in the coast of Jaffna Peninsula which lies in the Northern part of Sri Lanka. Out of the 121 specimens examined, 9 species under 5 genera in two families were documented in the coastal waters of both Valvettiturai to Point Pedro and the Jaffna lagoon waters. This includes Hydrophis fasciatus fasciatus which is no longer known in Sri Lanka increased the number of Hydrophis species to 8, thus the total number of sea snakes inhabiting the coastal waters of Sri Lanka become 14 in Hydrophiidae. Of the sea snakes collected, Lapemis curtus (33.88%) and Praescutata viperina (23.97%) were the commonly recorded species. Least recorded species were H. lapemoides, H. fasciatus fasciatus, Kerilia jerdonii jerdonii and Acrochordus granulatus (0.83, 0.83, 2.47 and 2.47%, respectively).